Intravenous treatment with human recombinant ApoA-I Milano reduces beta amyloid cerebral deposition in the APP23-transgenic mouse model of Alzheimer's disease - Fernández de Retana Alda, Sofía; Fatar, Marc; Grudzenski-Theis, Saskia (Neurobiology of aging, 2017)
Beyond the crucial role of apolipoprotein A-I (ApoA-I) on peripheral cholesterol metabolism, this apolipoprotein has also been implicated in beta amyloid (Aβ)-related neuropathologies. ApoA-I-Milano (M) is a mutated variant, which showed increased vasoprotective properties compared to ApoA-I-wild type in models of atherosclerosis and cardiovascular damage. We speculated that ApoA-I-M may also protect Aβ-affected vasculature and reverse some of the pathological features associated with Alzheimer's disease (AD). For this purpose, we produced and characterized human recombinant ApoA-I-wild type and ApoA-I-M proteins. Both of them were able to avoid the aggregation of Aβ in vitro, even though recombinant ApoA-I-M was significantly more effective in protecting endothelial cells from Aβ(1-42)-toxicity. Next, we determined the effect of chronic intravenous administration of rApoA-I-M in the APP23-transgenic mouse model of AD. We found reduced cerebral Aβ levels in mice that received rApoA-I-M, which were accompanied by a lower expression of astrocyte and microglia neuroinflammatory markers. Our results suggest an applicability of this molecule as a therapeutic candidate for protecting the brain in AD.